Financial Disparities Among Retail Employees: Financial Literacy, Income, Financial Behavior, and Personal Financial Planning - Rizky Tanaiyo; Hais Dama; Mohamad Agus Salim Monoarfa (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study was motivated by the suboptimal personal financial planning among Alfamart employees, despite their having a steady income and financial literacy. This study aims to analyze the influence of financial literacy and income on personal financial planning, with financial behavior as a mediating variable among Alfamart employees. The method used is a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis based on questionnaire data. The results show that financial literacy does not directly influence personal financial planning but does influence financial behavior. Income influences both financial behavior and personal financial planning, and financial behavior influences personal financial planning. Financial behavior fully mediates the relationship between financial literacy and financial planning, and partially mediates the relationship between income and financial planning. These findings confirm that financial behavior is a key factor in shaping well-directed financial planning. Keywords: financial literacy, income, financial behavior, personal financial planning, SEM-PLS, retail employees